The Role of Customer Engagement Mediation in the Relationship between Brand Image and Customer Satisfaction towards Customer Loyalty in Pahawang Island, Lampung - Vira Syavina; Maulana Agung P; May Roni (Cita konsultindo, 2025)
The diverse natural and cultural wealth in Indonesia has the potential to attract local and foreign tourists to support tourism development. This studies goal to check the impact of customer engagement mediation in the connection among brand image and customer satisfaction on customer loyalty. This study is based on consumer behavior theory and uses a quantitative approach through explanatory research stages. The specimen mode uses purposive sampling with the Cochran formula, so that 96 respondents are obtained. Data were collected by distributing questionnaires to visitors to Pahawang Island and the data were anatomize use smartPLS 4.0. The anatomize techniques used include outer model tests, iner model tests, and hypothesis tests. The studie outcome represent that brand image and customer satisfaction have a positive and significant effect on customer loyalty. Then the outcome of the studi also explain that customer engagement is able to mediate the relationship among brand image and customer satisfaction on customer loyalty in Pahawang Island, Lampung.